The Digital Revolution: Can Yogyakarta's Micro-Enterprises Ride the Wave? - Fridayani, Helen Dian; Chiang, Li Chun; Mahendro, Aldryan Bagaskara; Agustin, Martalia Susantiana (Faculty of Economic and Business, 2025)
Research Originality: This study enhances the comprehension of micro-enterprise owners who have transitioned to entrepreneurship by investigating their enhanced skills and flexibility in using digital technology.Research Objectives: This study examined the factors that influence technology adoption by business owners with experience in Microenterprises (MIEs). It also explored how digital technology's adoption mediates the relationship between these factors and the firm's performance.Research Methods: This study uses quantitative Path Analysis to examine the causal links between variables that impact the performance of micro-enterprises (MIEs) in Yogyakarta, Indonesia. A random sample of 461 MIE owners was selected.Empirical Results: The research found that micro-enterprises with organizational readiness and strategic orientation are more likely to use digital technology than those that do not adapt to or follow modern times. The cause was the high strategic orientation of Yogyakarta's MIEs.Implications: This study's empirical implication is to assess MIE development programmes in terms of digital technology usefulness within the context of business creation and technological transfer through MIEs in Yogyakarta.JEL Classification: C12, C31, O31How to Cite:Fridayani, H. D., Chiang, L. C., Mahendro, A. B., & Agustin, M. S. (2025). The Digital Revolution: Can Yogyakarta’s Micro Enterprise Ride the Wave. Etikonomi, 24(1), 191 – 204. https://doi.org/10.15408/etk.v24i1.37973.